Climate and dispersal limitation drive tree species range shifts in post-glacial Europe: results from dynamic simulations - Zani, Deborah; Lischke, Heike; Lehsten, Veiko (Frontiers in Ecology and Evolution, 2023)
The ability of species to colonize newly suitable habitats under rapid climate change can be constrained by migration processes, resulting in a shift of the leading edge lagging behind the ameliorating climate, i.e. migration lag. The importance and extent of such migration lags during the forest expansion after the Last Glacial Maximum (LGM) are still debated. Similarly, the relative importance of the main drivers of post-glacial vegetation dynamics (temperature, dispersal limitation, and competition) is still discussed in the literature.Methods: We used the dynamic global vegetation model LPJ-GM 2.0 to reconstruct the range shifts of 16 competing major European tree species after the LGM (18.5 ka BP) until recent times (0 ka BP). We simulated two dispersal modes by allowing free establishment whenever the climatic conditions suited the species (free dispersal), or by accounting for migration processes in the simulated vegetation dynamics (dispersal limitation). We then calculated thermal and range shift velocities, competition at establishment, thermal and dispersal lags for each species and dispersal mode. Finally, we compared our simulated range shift velocities with pollen-derived migration rates.The simulation assuming limited dispersal resulted in more accurate migration rates as compared to pollen-derived migration rates and spreading patterns. We found no marked migration lags in the post-glacial establishment of pioneer species (Pinus sylvestris and Betula pubescens). Under the free dispersal mode, the remaining temperate species expanded rapidly and almost synchronously across central Europe upon climate warming (Bølling-Allerød interstadial). Differently, the northward spread of temperate species simulated under dispersal limitation happened mainly during the Holocene and in successive waves, with late spreaders (e.g. Fraxinus excelsior) experiencing multi-millennial dispersal lags and higher competition. Discussion: Our simulation under dispersal constraints suggests that the post-glacial tree expansion in Europe was mainly driven by species-specific thermal requirements and dispersal capacity, which in turn affected the order of taxa establishment and thus the degree of competition. Namely, taxa with 2 This is a provisional file, not the final typeset article less cold-tolerance and relatively low dispersal ability experienced the highest migration lags, whereas the establishment of pioneer species was mostly in equilibrium with the climate.